Using petrographically observable microstructure to predict hydromechanical changes in a complex siliciclastic storage site during CO2 injection. (September 2022) - Simmons, Jason; Rinehart, Alex; Luhmann, Andrew; Mozley, Peter; Heath, Jason; Majumdar, Bhaskar
Highlights: Petrographically-observable textures inform the maintenance of mechanical strength under CO2 -fluid-rock interactions. CO2 -rich reservoir fluids induce substantial mineral dissolution and precipitation. Effluent of CO2 -rich injection was saturated with carbonates and phyllosilicates, indicating potential for late-term precipitation. Permeability of cores reacted with CO2 -rich reservoir fluids mostly increased. Despite significant mineralogical alterations, CO2 -fluid rock interactions did not result in loss of tensile strength. Abstract: The complex geologic history of sandstone CO2 storage sites can result in separate rock units that control chemomechanical weakening. Here we document the chemical and mechanical changes that may occur during CO2 injection operations, linking potential mechanical instability to diagenesis and burial history. Using Southwest Partnership Morrow B sandstone, we combined flow of either a CO2 -rich formation water or formation water through experimental cores followed by four indirect tensile strength tests per sample on siderite-chlorite- and kaolinite-cemented lithofacies. Coupled experiments were informed using petrography and µ-X-ray computed tomography. We found alteration of ankerite, siderite, chlorite, and calcite cement, and precipitation of an iron-rich phase in reacted samples. Alteration caused changes in hydraulic properties and elastic velocity, but no change in tensile strength. Tensile strength was maintained due to the low abundance and non-load-bearing texture of ankerite, the stability and precipitation of siderite prior to compaction, and the precipitation of calcite both before and during/after compaction. Results suggests that alteration of the Morrow B sandstone due to CO2 injection will enhance permeability near the wellbore with no increased risk of tensile failure, although intervals cemented with early diagenetic carbonate cement may be more susceptible to compaction. No weakening supports the long term sustainability of CO2 injection for EOR and climate change mitigation in the Farnsworth Unit.